Using music to develop peer interaction: an examination of the response of two subjects with a learning disability. - Hooper J (British Journal of Learning Disabilities, 2002)
The paper examines the response of two subjects who attended a programme of music activity therapy in which the music activities encouraged peer interaction. Music activity therapy was compared with a control condition (i.e. ball and target games). Both treatment conditions increased the level of positive interaction. The absence of negative interaction was also significant. The results affirmed the value of nonverbal interventions in encouraging interaction, and offered insights into the relationship between the two subjects.